How do Special Needs Children Learn Arithmetic Operations? Analysis Mathematics Learning Trajectory of Mentally Retarded Students Based on Constructivism Theory - Fitriya, Yeni; Eliasa, Eva Imania (Proceeding of International Conference on Special Education in South East Asia Region, 2023)
Mentally retarded students have different learning trajectories for understanding mathematics concepts. This study aims to analyze the learning trajectory of mentally retarded students based on constructivism theory. Through a qualitative approach with the natural observation method. The instruments used in this study were observation sheets, interviews, and documentation. From the three results, the data will be validated through a technical triangulation process to obtain research findings. This study involved three students from the 6th grade with mental retardation who obtained some learning trajectories in the multiplication operation. The first learning trajectory is carried out through the process of repeated addition according to the number being multiplied, even though conceptually it is incorrect. Second, use the stake (turus system) to write down the unit place, and last, use the stake (turus system) to write down the value of the whole number. In constructivism, mentally retarded students can build their own ideas to solve multiplication operations according to their own learning trajectories. The results of this study can be implicated in the learning process and as a hypothetical learning trajectory for mentally retarded students.